PENGARUH HARGA DAN PROMOSI MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN PADA UMKM SE’INDONESIA CABANG MAMPANG JAKARTA SELATAN - Muhamad Adiala Yasmin; Aris Ariyanto (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Abstract. This research aims to determine the effect of Price and Social Media Promotion on Purchase Decisions at UMKM Se’Indonesia, Mampang branch, South Jakarta. The method used is a quantitative method with an associative approach. The sampling technique employed is Random Sampling, a method where samples are determined based randomly, meaning anyone who happens to meet the researcher can be used as a sample, resulting in a total of 100 respondents. Data analysis includes validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis testing. The results of this research show that price (X1) has a positive and significant effect on purchase decisions (Y), with the regression equation Y = 12.023 + 0.686X1. The correlation coefficient value is 0.743, meaning both variables have a strong relationship, and the hypothesis test result shows t-count > t-table (5.847 > 1.984). Social media promotion (X2) also has a positive and significant effect on purchase decisions (Y), with the regression equation Y = 15.402 + 0.628X2. The correlation coefficient value is 0.727, indicating a strong relationship, and the hypothesis test result shows t-count > t-table (5.274 > 1.984). Simultaneously, price and social media promotion have a positive and significant effect on purchase decisions with the regression equation Y = 8.897 + 0.430X1 + 0.363X2, and a coefficient of determination of 65.2%, while the remaining 34.8% is influenced by other factors. The hypothesis test obtained an f-count > f-table (90.736 > 3.09); thus, Ha3 is accepted and Ho3 is rejected. This means that simultaneously, price and social media promotion have a positive and significant effect on purchase decisions at UMKM Se’Indonesia, Mampang branch, South Jakarta.